Tributação e benefícios fiscais : a importância do Estado no fomento de políticas que promovam o crescimento e desenvolvimento sustentável - Brito, Cícero Antonio Mesquita da Silva (2021)
This dissertation is the result of research carried out in the city of Caldas Novas, located in the State of Goiás, regarding sustainability in thermal water tourism. The primary objective was to identify taxes with environmental characteristics, and also to verify how they are being used to achieve the business sustainability of tourism in the region. It consists of four chapters in the form of scientific articles. The first chapter makes a bibliographic review in order to show how the situation of Brazilian tax laws is in relation to environmental preservation. It provides an overview of the main tax laws in force today, showing the recommendations of international bodies in relation to the environment, in addition to checking how these laws are applied in practice. The methodology used was the reading of the main authors on the theme, in order to outline the theoretical profile that supported the research. The second chapter deals with the legal principles adopted by the Brazilian State as a form of environmental protection. It provides an overview of the legal principles used for environmental protection, in addition to recent research showing the practice of these principles. The third is a study focused on the city of Caldas Novas, aiming to show how the sustainability situation is found in tourism that explores the thermal waters, as well as the application of the ecological ICM rates in the municipality. Take a look at the tax agencies of the state of Goiás and the city of Caldas Novas.